Modulation technique for integrated broadband wireless applications - Syed Yusuf, Sharifah Kamilah (UTM, 2006)
The increasing demand on high bit rate and reliable wireless system has led to many new emerging modulation techniques. One of the techniques will be Orthogonal Frequency Division Multiplexing (OFDM), which offers reliable high bit rate wireless system with reasonable complexity. The primary reasons OFDM is preferred in most high bandwidth efficiency transmission systems are because it effectively resist Intersymbol Interference (ISI) and is robust towards multipath fading. Nevertheless, several of the main factors affecting the performance of an OFDM system are high Peak to Average Power Ratio (PAPR), phase noise and frequency offset. This project developed a communication system based on OFDM modulationtechnique. The system employs Block Coding scheme in reducing the PAPR of the OFDM system. The capability of Block Coding scheme to reduce the Bit Error Rate (BER) in an OFDM system was also measured. The performance of OFDM was accessed by using computer simulations performed using two of the Matlab tools which are Simulink and GUIDE.